Evaluación de tres protocolos de inseminación artificial a tiempo fijo (IATF) en vacas holstein friesian en la serranía ecuatoriana. - Benavides Cueva, Oscar Raúl (2021)
The study was developed in four dairy farms in the Ecuadorian Sierra, with an altitude ranging from 2,800 to 3,590 meters above sea level, in order to evaluate three FTAI protocols with the traditional one, in 27 heifers in each production system, with a total of 108 animals. Virgin heifers were selected where an experimental investigation was applied with a completely random design and Duncan when there is a difference, the T0 usual management of FTAI, the T1 with eCG day 9, T2 with Ecg day 7, T3 with GnRH as ovulatory hormone, the Body condition of the 108 animals is normal and homogeneous for the investigation where the means for T0 with 2.85, T1 with 2.8, followed by T3 with 2.81 and with less body weight T2 with 2.79 since the CC directly affects physiological and reproductive aspects with a percentage of cyclical animals of 61.1% and cyclical animals with 38.9%, the ovulatory response establishes treatment 1 of eCG day 9 or after removing the implant with 49.04 }0.54(a) the best in terms of hours of heat presence, and coincides with gestation with an average of animals that did not gestate of 3.19}1.22(a) followed by the variants in the protocols of IATF. In terms of economic value, eCG treatments are more expensive than BE, GNRH.